2012
DOI: 10.1007/s00264-012-1514-9
|View full text |Cite
|
Sign up to set email alerts
|

Modified tension band for displaced type 2 lateral end clavicle fractures

Abstract: Purpose Displaced type 2 lateral end clavicle fractures have a tendency to delayed union or non-union. Various methods of stabilisation of the displaced lateral end fractures are described. The increasing use of implants to fix such fractures also necessitates extensive dissection for implant retrieval. Adequate reduction and minimal tissue trauma during implant placement and removal would be ideal modalities for fixation of such fractures. Methods All displaced type 2 lateral end clavicle fractures fulfilling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…Therefore, the K-wire needs to be removed before active mobilization. For maintaining the reduction after removal of K-wire, Rijal et al 14) suggested additional figure-eight tension band techniques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the K-wire needs to be removed before active mobilization. For maintaining the reduction after removal of K-wire, Rijal et al 14) suggested additional figure-eight tension band techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors therefore suggested modified combined techniques, such as tension band with transacromial K-wire, and CC ligament suture augmentation with locking plate, with satisfactory clinical results. [14][15][16] However, the optimal treatment for type II fracture is still controversial.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Though it was a relatively small cohort study, good outcome and minimal complications were reported for this technique, which requires minimal incision and dissection and provides stable fixation of the fracture. [11] Another method of fixation is open reduction and endobutton fixation.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Though it was a relatively small cohort study, good outcome and minimal complications were reported for this technique, which requires minimal incision and dissection and provides stable fixation of the fracture. [11] Another method of fixation is open reduction and endobutton fixation. [12] This technique allows reduction and internal fixation of the fracture using sutures that pass through an endobutton placed in the clavicle and coracoid process and has shown good short and medium term outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…lateral end of clavicle modified tension banding techniques with transacromial Kirschner wires or suture anchors. 13,14 . hook plates, which are not only very reliable for union, but also can have complications, including rotator cuff tear, 15 impingement pain 16 and need for removal.…”
Section: Introductionmentioning
confidence: 99%